DEBIT CREDIT FRAMING EFFECT IN THE INVESTMENT ALOCATION DECISION - Mujilan, Agustinus (KINERJA, 2017)
This study aims to test the effect of accounting information in the investment decision if information is framed in debit or credit. Also, this study attempts to develop or formulate the framing instruments that essenced in accounting debit credit concept. The quasi experiment is applied for undergraduate accounting students. Wilcoxon ranks test is applied to test the data. The results show that there are framing effects which asset information is more favorable than liabilities, revenue information is more favorable than asset, and equity information is more favorable than asset. There is a tendency that revenue information is more favorable than expenses. This research means that there is framing effect in the accounting information when information is given separately only debit or credit, it should be reduced by giving complete information of debit credit transactions.